FEATURES OF MODERN WEB APPLICATION TESTING - BAHRІI, Ruslan; PETROVSKY, Serhii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
This paper investigates the technology and approaches to testing web applications in modern frameworks. The main techniques of manual testing, which require a large amount of manual work, are considered. The disadvantages of implementing the black-box testing method include the development of a formal specification, and the application of the white-box testing method requires analysis of software code.Particular attention is given to automated testing technologies, which are proposed to be used to develop sites in modern frameworks. The Test pyramid and test levels are described in detail, and the main advantages and disadvantages of each level are analyzed. At the first level, a set of tests consists of unit tests that verify that an individual unit is working correctly according to the requirements of the specification. At the second level of the automation pyramid - integration tests check the interaction of a fragment of code with external components. At the third level - end-to-end tests perform testing of various user scenarios, and UI tests check the correct operation of the web application interface.It is proposed to use behavioral development technology (BDD) for automated testing of web applications. BDD focuses on studying problems formulated based on customer stories and the construction of logic and tests based on these problems. BDD tests are best worked for integration testing, which involves testing different user scenarios.A dependency injection (DI) design template has been used to improve the efficiency of the web application development process, with tools built into modern frameworks. This template applies the transfer of dependencies to an external, specially designed software component. Dependence is injected using a special IoC container.
Keywords: computer science; testing; framework; web applications